Robert Lepage's Scenographic Dramaturgy The Aesthetic Signature at Work - Poll, Melissa (Adaptation in Theatre and Performance, 2018)
This book theorizes auteur Robert Lepage's scenography-based approach to adapting canonical texts. Lepage's technique is defined here as 'scenographic dramaturgy', a process and product that de-privileges dramatic text and relies instead on evocative, visual performance and intercultural collaboration to re-envision extant plays and operas. Following a detailed analysis of Lepage's adaptive process and its place in the continuum of scenic writing and auteur theatre, this book features four case studies charting the role of Lepage's scenographic dramaturgy in re-'writing' extant texts, including Shakespeare's Tempest on Huron-Wendat territory, Stravinsky's Nightingale in a twenty-seven ton pool, and Wagner's Ring cycle via the infamous, sixteen-million-dollar Metropolitan Opera production. The final case study offers the first interrogation of Lepage's twenty-first century 'auto-adaptations' of his own seminal texts, The Dragons' Trilogy and Needles & Opium. Though aimed at academic readers, this book will also appeal to practitioners given its focus on performance-making, adaptation and intercultural collaboration.